Burnout Levels of Handball Players with Respect to Age, Gender and Experience - TOROS, Turhan (Asian Journal of Education and Training, 2018)
The aim of this study was to investigate burnout levels of handball players in terms of age, gender and experience. In this study, 116 female and 128 male, totally 244 handball players with the mean age 22.39±1.98 year participated voluntarily. Maslach Burnout Inventory that originally developed by Maslach and Jackson (1981) and adapted to Turkish population by Ergin (1992) was used for measuring the burnout levels of handball players. The data of this research analyzed with SPSS package program and to test the internal consistency of the scale, Cronbach Alpha coefficient was calculated. According to the binary group comparisons, it was determined that the data were not normally distributed and therefore Mann Whitney U test was used. And also, The Kruskall Wallis H test was used for the multiple group comparisons. According to Mann Whitney U test results, there were no significant differences in emotional burnout (p=.088, p>.05), depersonalization (p =.411, p>.05) and personal accomplishment (p=.503, p>.05) between male and female handball players. According to Kruskall Wallis H test results, there were no significant differences in emotional burnout (p=.152; p>.05), depersonalization (p=.310; p>.05) and personal accomplishment (p=.301, p>.05) sub dimensions according to age and no significant difference was found in the subscale of personal accomplishment (p=.641; p> .05) according to the experience variable. But, there were statistically significant difference in emotional burnout (p=.003; p<.05) and depersonalization (p=.008; p<.05) sub - dimensions according to experience variable. As a result, burnout level and depersonalization are thought to be important in terms of the experience of handball players.